Initial Real-World Pilot of the MedMorph Reference Architecture: Hepatitis C Surveillance and Research - Michaels, Maria; Botts, Nathan E.; Hassell, Susan; Mardon, Russell; Pan, Eric Chung Ren; Flanigan, Mike; Chehab, Chirine; Liu, Sara; Bocour, Angelica; Alexander, Mark; Aponte, Angel; Thompson, Nicola D. (Applied Clinical Informatics, 2025)
Objectives This study aimed to demonstrate real-world use of the Making Electronic Data More Available for Research and Public Health (MedMorph) Reference Architecture (RA) for automated exchange of hepatitis C-related data for public health surveillance and research using Fast Healthcare Interoperability Resources (FHIR).Methods Pilot participants included a public health authority (PHA), research organization (RO), clinical sites, and electronic health record (EHR) vendors. The RA was tested for hepatitis C public health surveillance and research data exchange. A mixed methods evaluation used multiple data sources to assess impact of the RA compared with usual methods.Results After implementation of the RA components, there was no burden on clinical staff to report data for public health surveillance or research purposes. Data were successfully transferred and passed from EHR to PHA and RO, which revealed the value of receiving clinical data in addition to laboratory data via electronic laboratory reporting for the PHA and limitations in the Bulk FHIR standard.Conclusion Initial results indicate potential for long-term reduction of level of effort of reporting while improving the availability and completeness of clinical data for public health surveillance and research. Using a FHIR-based approach that aligns with regulatory health information technology certification requirements and existing infrastructure may reduce implementation burden. The MedMorph approach can enhance public health surveillance and research, resulting in improved data completeness and reduced reporting burden through automated data exchange using industry standards. MedMorph will continue to inform Centers for Disease Control and Prevention's Public Health Data Strategy, which provides the agency's direction for data modernization.
Keywords: implementation and deployment; FHIR; public health; infectious disease; clinical research informatics; testing and evaluation; facilitators and barriers; monitoring and surveillance; EHRs and systems; data processing